Electrolytic capacitors
By controlling the carbon attachment on the cathode foil to less than 37.5μg/cm², the capacitor prevents short circuits and maintains insulation, addressing the issue of carbon-induced performance fluctuations in electrolytic capacitors.
Patent Information
- Application Number
- JP2021019022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-02-09
AI Technical Summary
Existing electrolytic capacitors face issues with short circuits between the anode and cathode foils due to carbon separation from the cathode foil, which adversely affects the insulation function of the separator.
The capacitor design includes a cathode foil with a controlled amount of carbon, specifically less than 37.5μg/cm², attached only to the pole side surface or partially on the cathode side surface, to minimize carbon release into the separator.
This design inhibits carbon entry into the separator, maintaining insulation properties and reducing performance fluctuations by regulating carbon movement, thereby enhancing the capacitor's performance and reducing equivalent series resistance.
Smart Images

Figure 0007604930000003 
Figure 0007604930000004 
Figure 0007604930000005
Abstract
Description
[Technical field]
[0001] The present disclosure includes a cathode foil having a carbon layer formed thereon. electrolytic Regarding capacitors. [Background technology]
[0002] An electrolytic capacitor includes an anode foil, a cathode foil, and a separator disposed between the anode foil and the cathode foil, and is capable of storing electricity. In such electrolytic capacitors, it is known that a carbon layer is formed on the cathode foil (for example, Patent Document 1). The carbon layer has the effect of increasing the electrostatic capacitance of the cathode foil, for example. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2006-80111 A Summary of the Invention [Problem to be solved by the invention]
[0004] In capacitors such as electrolytic capacitors, it is necessary to prevent short circuits between the anode foil and the cathode foil. If a large amount of carbon is detached from the cathode foil, there is a concern that it may adversely affect the insulating function of the separator. Patent Document 1 does not disclose or suggest such a problem, and the configuration disclosed in Patent Document 1 cannot solve such a problem.
[0005] Therefore, the present disclosure includes, for example, a cathode foil on which a carbon layer is formed. electrolytic Separators suitable for capacitors or containing such separators electrolytic The present invention aims to provide a capacitor. [Means for solving the problem]
[0006] In order to achieve the above object, according to one aspect of the present disclosure, electrolytic The capacitor includes an anode foil, a cathode foil, and a separator disposed between the anode foil and the cathode foil. The cathode foil includes a carbon layer, and the carbon attached to the separator is 37.5 μg / cm 2 is less than.
[0007] the above electrolytic In the capacitor, the carbon adhesion amount is 0.375 μg / cm 2 More than 37.5μg / cm 2 It may be less than that.
[0008] the above electrolytic In the capacitor, the carbon ,shadow It may be attached only to the electrode surface.
[0009] the above electrolytic In the capacitor, the carbon ,shadow It may be disposed over the entire electrode side surface, or may be disposed partially over the cathode side surface. Effect of the Invention
[0010] According to the above aspect of the present disclosure, any of the following effects can be obtained.
[0011] (1) The amount of carbon attached to the separator is 37.5 μg / cm 2 By setting the thickness to less than this, the carbon released from the cathode foil is prevented from penetrating into the separator, and the insulating properties of the capacitor can be maintained.
[0012] (2) The carbon that breaks off from the cathode foil is less likely to penetrate into the separator, and is more likely to be trapped between the cathode foil and the separator. This restricts the movement of carbon, making it easier to achieve smaller fluctuations in the performance of the capacitor. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a diagram illustrating an example of a capacitor according to an embodiment. [Diagram 2]FIG. 1 shows experimental samples and measurements of conduction resistance. [Diagram 3] 1 is a table showing the conductive resistance values of the experimental samples. [Figure 4] 1 is a graph showing the conductive resistance values of the experimental samples. [Diagram 5] FIG. 5 is an enlarged view of a range V shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Fig. 1 shows an example of a capacitor according to an embodiment. In Fig. 1, an outer case, a sealing member, and an electrolyte of the capacitor are omitted. Fig. 1B is an enlarged view of a range IB shown in Fig. 1A. The configuration shown in Fig. 1 is an example, and the technology of the present disclosure is not limited to such a configuration.
[0015] The capacitor 2 is an example of an electronic component, such as an electrolytic capacitor. The capacitor 2 includes a capacitor element 4, a terminal lead 6, an exterior case, and a sealing member. The terminal lead 6 is connected to the capacitor element 4 and protrudes from one end face of the capacitor element 4. The capacitor element 4 and a portion of the terminal lead 6 are inserted into the interior of the exterior case. The sealing member is placed in the opening of the exterior case to seal the interior of the exterior case. In other words, the capacitor element 4 and a portion of the terminal lead 6 are sealed inside the exterior case. The terminal lead 6 passes through a through hole in the sealing member and protrudes from the sealing member.
[0016] The capacitor element 4 includes an anode foil 12, a cathode foil 14, a separator 16, and an electrolyte. The anode foil 12 and the cathode foil 14 are each connected to a different terminal lead 6. The anode foil 12, the cathode foil 14, and the separator 16 are stacked and wound so that the separator 16 is disposed between the anode foil 12 and the cathode foil 14 to form a wound element. This wound element forms the capacitor element 4. The voids in the capacitor element 4 and the separator 16 are filled with an electrolyte. The electrolyte may be an electrolyte solution or a gel electrolyte, may include an electrolyte solution and a gel electrolyte, or may include an electrolyte solution or a gel electrolyte and a solid electrolyte. The solid electrolyte includes, for example, a conductive polymer.
[0017] The anode foil 12 constitutes an anode-side electrode of the capacitor 2. The anode foil 12 is, for example, a valve metal foil such as a tantalum foil or an aluminum foil, and is, for example, a strip-shaped foil. The surface of the anode foil 12 has irregularities formed, for example, by etching, and includes a dielectric oxide film formed, for example, by chemical conversion treatment. The irregularities formed by etching have, for example, a porous structure.
[0018] The cathode foil 14 constitutes an electrode on the cathode side of the capacitor 2. The cathode foil 14 is, for example, a strip-shaped foil, and includes a main foil 18 and a carbon layer 20. The main foil 18 is, for example, a valve metal foil such as an aluminum foil, a tantalum foil, a niobium foil, a titanium foil, a hafnium foil, a zirconium foil, a zinc foil, a tungsten foil, a bismuth foil, or an antimony foil. The surface of the main foil 18 has irregularities formed, for example, by etching, and the surface area of the main foil 18 is enlarged. The surface of the main foil 18 may include, for example, tunnel-shaped or spongy etching pits, and the tunnel-shaped or spongy etching pits may form the irregularities.
[0019] The carbon layer 20 is disposed, for example, on both sides of the main foil 18. The carbon layer 20 may be disposed on only one side of the main foil 18. The carbon layer 20 is in close contact with the unevenness of the main foil 18. In other words, the carbon layer 20 is disposed on the outside of the main foil 18, and the cathode foil 14 has a two-layer structure of the main foil 18 and the carbon layer 20, or a three-layer structure in which the carbon layers 20 are disposed on both sides of the main foil 18. The carbon layer 20 contains a carbon material as a main material, and further contains a binder and a dispersant as additives.
[0020] The carbon material is, for example, spherical carbon. The spherical carbon functions as an active material. Therefore, the carbon layer 20 includes an electric double layer active material layer made of spherical carbon, and increases the capacitance of the cathode foil 14.
[0021] The spherical carbon includes carbon black such as, for example, Ketjen black, acetylene black, channel black, and thermal black.
[0022] The carbon material may be a mixture containing the aforementioned spherical carbon and graphite. The graphite may be, for example, natural graphite, artificial graphite, or graphitized Ketjen black, and may have a shape such as a flake, a lump, a clay, a sphere, or a thin plate. The graphite is preferably flake or thin, and the aspect ratio of the short diameter to the long diameter of the graphite is preferably in the range of 1:5 to 1:100. The flake or thin plate graphite having the aforementioned aspect ratio can, for example, push the spherical carbon into the etching pit, and a part of the carbon layer 20 can be formed up to the inside of the etching pit. Therefore, the carbon layer 20 can be firmly attached to the main foil 18 by the anchor effect.
[0023] When the average particle size of the graphite is 6 μm or more and 10 μm or less, it is possible to obtain an effect such as suppressing the decrease in capacitance due to high-temperature environmental load. Furthermore, when the average particle size of the graphite is 6 μm or less, it is possible to increase the capacitance of the capacitor 2 while suppressing the decrease in capacitance due to high-temperature environmental load. Furthermore, when the average particle size of the graphite is 6 μm or less, it becomes easy to keep the graphite in the carbon layer 20, and the amount of binder added can be suppressed. By suppressing the amount of binder added, the ratio of carbon material increases. Therefore, it is possible to reduce the electrical resistance of the cathode foil 14, and the equivalent series resistance (ESR) of the capacitor 2 can be reduced. Note that the numerical value of the average particle size described above is a numerical value based on the median diameter, so-called D50.
[0024] When the carbon material is a mixture of graphite and spherical carbon, in order to obtain the effect of using graphite and spherical carbon in combination, the mass ratio of graphite to the mixture of graphite and spherical carbon [mass of graphite / (mass of graphite+mass of spherical carbon)] is, for example, in the range of 25% or more and 90% or less.
[0025] The binder is, for example, styrene butadiene rubber, polyvinylidene fluoride, or polytetrafluoroethylene, and binds the graphite and the spherical carbon. The dispersant is, for example, sodium carboxymethyl cellulose. The carbon layer 20 is made, for example, from an aqueous solution in which the spherical carbon is dispersed. The dispersant can disperse the spherical carbon in the aqueous solution.
[0026] Separator 16 is disposed between anode foil 12 and cathode foil 14 to prevent a short circuit between anode foil 12 and cathode foil 14. Separator 16 has an anode side surface 22-1 in contact with anode foil 12 and a cathode side surface 22-2 in contact with cathode foil 14, and includes a separator body 24 and carbon 26.
[0027] The separator body 24 is an insulating material, and includes separator members such as kraft, manila, esparto, hemp, rayon, cellulose, mixtures thereof, etc. The separator body 24 may be, for example, a commercially available separator.
[0028] The carbon 26 adheres to the cathode side surface 22-2. That is, the cathode side surface 22-2 includes the surface of the separator body 24 on the cathode foil 14 side and the carbon 26. The carbon 26 is, for example, sandwiched between a plurality of small gaps on the surface of the separator body 24 and scattered on the cathode side surface 22-2. The carbon 26 may, for example, cover the entire surface of the separator body 24 on the cathode foil 14 side and be disposed on the entire cathode side surface 22-2. That is, the carbon 26 may be disposed partially on the cathode side surface 22-2 or may be disposed on the entire cathode side surface 22-2. The carbon 26 sandwiched between the gaps blocks the gaps of the separator body 24 and can, for example, prevent the detached carbon detached from the cathode foil 14 from penetrating into the inside of the separator 16. The carbon 26 covering the surface of the separator body 24 can, for example, prevent the detached carbon from penetrating into the inside of the separator 16. The amount of carbon 26 attached may be an amount necessary for carbon 26 to fill some of the gaps on the surface of separator body 24, and may be, for example, 0.375 μg / cm 2 The amount of carbon 26 attached is preferably 37.5 μg / cm 2 or more, based on the results of the experiment shown below. 2 It is preferable that the unit is less than μg / cm 2 " represents the mass of carbon 26 attached per square centimeter of the separator 16. 2 When the carbon 26 is less than 37.5 μg / cm 3 , the effect of suppressing short circuits between electrodes can be expected, regardless of the type, density, or thickness of the separator body 24. 2 If the amount is more than this, some types, densities, or thicknesses of the separator may result in separators that are not suitable for use as the separator body 24 .
[0029] The amount of carbon adhering to the separator 16 can be determined, for example, by the following method. That is, the separator 16 removed from the capacitor 2 is washed with, for example, ethanol to remove the electrolyte from the separator 16. The separator 16 from which the electrolyte has been removed is dried. The dried separator 16 is thermally analyzed by an existing analytical method such as thermogravimetric analysis (TGA) or thermogravimetric-differential thermal analysis (TG-DTA) to determine the amount (weight or mass) of the carbon 26 adhering. The obtained weight or mass is divided by the analyzed area of the separator 16 to determine the amount of carbon per square centimeter of the separator.
[0030] The terminal leads 6 are formed of, for example, a metal having good electrical conductivity. One terminal lead 6 is an anode side terminal and is connected to the anode foil 12 by, for example, cold welding or stitch connection. The other terminal lead 6 is a cathode side terminal and is connected to the cathode foil 14 by, for example, cold welding or stitch connection.
[0031] The sealing member is formed of, for example, insulating rubber. The sealing member has insertion holes at positions corresponding to the terminal leads 6. The terminal leads 6 of the capacitor element 4 pass through the insertion holes of the sealing member and are exposed to the outside of the capacitor 2.
[0032] The exterior case is, for example, a cylindrical aluminum case with a bottom. [Capacitor manufacturing process]
[0033] The manufacturing process of capacitor 2 is an example of a method for manufacturing a capacitor of the present disclosure, and includes, for example, a step of making anode foil 12, a step of making cathode foil 14, a step of making separator 16, a step of making capacitor element 4, and a step of encapsulating capacitor element 4.
[0034] In the process of producing the anode foil 12, the surface of a valve metal foil such as a tantalum foil or an aluminum foil is etched to form projections and recesses on the surface of the valve metal foil. The valve metal foil after the etching process is subjected to a chemical conversion process to form a dielectric oxide film on the surface of the valve metal foil. The valve metal foil is etched by applying a current to the valve metal foil immersed in an aqueous chloride solution such as hydrochloric acid or salt. The applied current may be either a direct current or an alternating current. The valve metal foil is chemically converted by applying a voltage to the valve metal foil immersed in an electrolyte solution containing a solution of ammonium borate, ammonium borate, ammonium phosphate, ammonium adipate, or the like. The chemically converted valve metal foil is cut to produce the anode foil 12.
[0035] In the process of producing the cathode foil 14, the surface of a valve metal foil such as aluminum foil, tantalum foil, niobium foil, titanium foil, hafnium foil, zirconium foil, zinc foil, tungsten foil, bismuth foil, or antimony foil is etched to form irregularities on the surface of the valve metal foil. The etching on the cathode foil 14 side may be the same as or different from the etching on the anode foil 12 side. A carbon layer 20 is formed on the etched valve metal foil, and the valve metal foil with the carbon layer 20 formed thereon is cut to produce the cathode foil 14.
[0036] The carbon layer 20 is produced as follows. The carbon material, binder, and dispersant described above are added to a dilution liquid, and mixed by a dispersion process such as a mixer, jet mixing (jet collision), ultracentrifugation, or ultrasonic treatment to form a slurry. The binder is added, for example, in an amount necessary for binding the carbon material, and the dispersant is added, for example, in an amount necessary for dispersing the carbon material. Therefore, the amounts of the binder and dispersant added are smaller than the amount of the carbon material added. When graphite is used as the carbon material, the graphite may be pulverized by a pulverizer such as a bead mill or a ball mill to adjust the average particle size of the graphite before adding it to the dilution liquid.
[0037] The diluent is, for example, an alcohol, a hydrocarbon solvent, an aromatic solvent, an amide solvent, water, or a mixture thereof. The alcohol is, for example, methanol, ethanol, or 2-propanol. The amide solvent is, for example, N-methyl-2-pyrrolidone (NMP) or N,N-dimethylformamide (DMF).
[0038] The slurry is applied to the valve metal foil after etching. After drying, the slurry is pressed. The carbon material is aligned by pressing. If the carbon material contains graphite, the graphite is aligned by pressing and is deformed to conform to the irregularities of the valve metal foil. When the graphite is pressed against the irregularities, the spherical carbon is pushed into the pores of the valve metal foil. This causes the slurry to adhere to the valve metal foil, and a carbon layer 20 that adheres to the main foil 18 is obtained.
[0039] In the process of manufacturing the separator 16, the above-described separator member is cut to manufacture the separator 16. Note that the adhesion of the carbon 26 to the separator 16 may occur, for example, after the separator 16 comes into contact with the cathode foil 14.
[0040] In the process of producing capacitor element 4, terminal leads 6 are connected to anode foil 12 and cathode foil 14, respectively. A first separator 16 is disposed between anode foil 12 and cathode foil 14, and a second separator 16 is disposed on the outside of anode foil 12 or cathode foil 14. Capacitor element 4 is produced by winding anode foil 12, cathode foil 14, and first and second separators 16.
[0041] In the process of sealing the capacitor element 4, the capacitor element 4 impregnated with an electrolyte such as an electrolytic solution is inserted inside an exterior case, and then a sealing member is attached to the opening of the exterior case, thereby completing the capacitor 2. [Experimental Example]
[0042] In order to confirm the preferable range of the amount of carbon 26 attached, the electrical resistance of the experimental separator 32 (FIG. 2) to which carbon 26 was attached was confirmed.
[0043] In order to produce the experimental separator 32 to which the carbon 26 is attached, slurries 1 to 10 having the solid content concentrations shown in Table 1 are prepared. The components of the slurries 1 to 10 are as follows. Carbon: Carbon black powder Binder: Styrene butadiene rubber Dispersant: Sodium carboxymethylcellulose aqueous solution Diluent: Pure water The amounts of binder and dispersant added are sufficiently small compared to the amount of carbon added, so the amount of solids in Slurries 1 to 10 can be considered to be equal to the amount of carbon. [Table 1]
[0044] 10 μL (microliters) of any of the slurries 1 to 10 was evenly dropped onto a 1 cm square surface of the experimental separator 32, and the experimental separator 32 and the slurry were heated to 80° C. to obtain an experimental separator 32 with carbon 26 attached thereto. The experimental separator 32 was any of the separators S1 to S18 (manufactured by Nippon Kodo Paper Co., Ltd.) shown in Table 2. Since the solid concentration of the slurries 1 to 10 is low, the specific gravity of the slurries 1 to 10 can be considered to be equal to the specific gravity of water. Therefore, the carbon attachment amount CA when 10 μL of each of the slurries 1 to 10 was dropped onto the separator can be considered to be the amount shown in Table 1. [Table 2] The materials of the separator are as follows: Separators S1 to S6: Kraft Separator S7: (High density side) Kraft papermaking (Low density side) Cotton linter and hemp blend paper Separator S8: Manila and Esparto blend paper Separator S9: Manila hemp Separator S10~S13: Manila and esparto blend paper Separator S14: A blend of nylon and fibrillated acrylic fibers Separator S15~S18: Special rayon The kraft paper of separator S7 and the mixed paper of separator S14 are coated with polyvinyl alcohol (PVA) on the surface facing the anode foil.
[0045] Figure 2 shows an example of measuring the conduction resistance. In Figure 2, the fixing by the clip is omitted.
[0046] The experimental separator 32 with the carbon 26 attached thereto is sandwiched between two copper foils 34 from above and below, and the experimental separator 32 and the copper foils 34 are sandwiched between two glass slides 36, which are then fixed with clips to obtain an experimental sample 38. The experimental separator 32 protrudes outside at least one of the copper foils 34 so that the two copper foils 34 do not come into direct contact with each other.
[0047] An insulation resistance meter is connected to the two copper foils 34 to measure the resistance (conductivity resistance) of the experimental sample 38. In the portion where only the experimental separator 32 is placed between the copper foils 34, the resistance is outside the measurement range, for example, 500 MΩ (megohms) or more. Therefore, by measuring the resistance of the experimental sample 38, the effect of the carbon 26 on the insulation properties of the separator can be understood.
[0048] FIG. 3 shows a table of the conductive resistance values of the experimental samples. FIG. 4 shows a graph of the conductive resistance values of the experimental samples, and FIG. 5 is an enlarged view of the range V shown in FIG. 4. In FIG. 4 and FIG. 5, the conductive resistance values of the experimental sample 38 including the separators S1, S8 to S10, and S14 to S17 are shown. In FIG. 3, "OR" is an abbreviation for "out of range" indicating that the conductive resistance value exceeds 500 MΩ and is outside the measurement range. Also, in FIG. 3, for example, 1 MΩ and 100 MΩ are represented as "1.00. E+06" and "1.00. E+08", respectively.
[0049] In this experimental example, the adhesion amount CA of carbon 26 is 37.5 μg / cm 2 It was found that when the adhesion amount of carbon 26 was less than 37.5 μg / cm 2 , the conductive resistance value of all the test samples 38 was 100 MΩ or more. In addition, from the graphs shown in FIG. 4 and FIG. 5 , it was found that when the adhesion amount of carbon 26 was less than 37.5 μg / cm 2 , the conductive resistance value of all the test samples 38 was 100 MΩ or more. 2 It was found that the conductive resistance value of the experimental separator 32 decreased when the amount of carbon 26 was more than 37.5 μg / cm 2 . 2 Preferably less than 37.5 μg / cm 2 By keeping the thickness of the electrodes at 1000 to 1500 nm, a significant effect of preventing short circuits of the electrodes can be expected.
[0050] According to the above embodiment, for example, the following effects can be obtained.
[0051] (1) The amount of carbon attached to the cathode side surface 22-2 of the separator 16 is 37.5 μg / cm 2 Since the amount of carbon separated from the cathode foil 14 is less than 100%, the carbon is less likely to penetrate into the separator 16. The penetration of carbon into the inside of the separator 16 is suppressed, and the insulating properties of the capacitor 2 can be maintained.
[0052] (2) The detached carbon is less likely to penetrate into the separator 16 and is more likely to be retained between the cathode foil 14 and the separator 16. The movement of the carbon is restricted, and the effect of reducing the performance fluctuation of the capacitor 2 is more likely to be obtained.
[0053] (3) Since the carbon layer 20 of the cathode foil 14 is in direct contact with the separator 16, the effect of reducing the resistance of the cathode foil 14 and therefore reducing the equivalent series resistance of the capacitor 2 can be easily obtained.
[0054] Regarding the embodiment described above, characteristics and modifications thereof will be listed below.
[0055] (1) In the above embodiment, capacitor element 4 is a wound element. However, capacitor element 4 may be a laminated element in which, for example, a plurality of flat anode foils, cathode foils, and separators are laminated.
[0056] (2) The materials of the anode foil 12, the cathode foil 14, the separator 16, the exterior case, the sealing member, and the electrolyte are not limited to those described in the above embodiment. These materials may be other materials used in aluminum electrolytic capacitors or similar capacitors. For example, a separator may be sandwiched between an anode foil and a cathode body to which an aluminum tab-shaped lead-out terminal is ultrasonically connected, and then these may be wound to form a capacitor element. A phenol laminate with an external terminal attached may be used as the sealing member, and the aforementioned capacitor element may be impregnated with an electrolyte, and then the lead-out terminal led out from the capacitor element may be connected to the external terminal of the sealing member, or the capacitor element and the sealing member may be inserted into an exterior case and sealed with the sealing member. In addition, the material of the carbon layer 20 is not limited to those described in the above embodiment. The material forming the carbon layer 20 may be any conductive material.
[0057] As explained above, the most preferred embodiment of the present disclosure has been described, however, the present disclosure is not limited to the above description, and it goes without saying that those skilled in the art can make various modifications and changes based on the gist of the invention described in the claims or disclosed in the specification, and such modifications and changes are naturally included in the scope of the present disclosure. [Industrial Applicability]
[0058] The technology of the present disclosure can be usefully used for insulating electrodes that include a conductive material such as carbon. [Explanation of symbols]
[0059] 2. Capacitor 4 Capacitor elements 6 Terminal Lead 12 Anode foil 14 Cathode foil 16 Separator 18 Main body foil 20 Carbon Layer 22-1 Anode surface 22-2 Cathode surface 24 Separator body 26 Carbon
Claims
1. 1. An electrolytic capacitor comprising an anode foil, a cathode foil, and a separator disposed between the anode foil and the cathode foil, the cathode foil includes a carbon layer; The carbon attached to the separator is 37.5 μg / cm 2 The electrolytic capacitor according to claim 1, wherein
2. The amount of carbon attached is 0.375 μg / cm 2 37.5μg / cm or more 2 2. The electrolytic capacitor of claim 1, wherein the
3. 3. The electrolytic capacitor according to claim 1, wherein the carbon is attached only to the surface of the cathode.
4. 4. The electrolytic capacitor according to claim 1, wherein the carbon is disposed on the entire surface of the cathode side, or is disposed on a part of the surface of the cathode side.
Citation Information
Patent Citations
Aluminum electrolytic capacitor and its manufacturing method
JP2006080111A
Solid electrolytic capacitor
JP2007042732A
